(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The paper’s aim is to investigate the influence of added light absorber (Tinuvin® 327) on dimension accuracy of three-dimensional (3D) micro-parts manufactured by a dynamic mask projection microstereolithography (µSL) system. One of the common problems with stereolithography systems, and particularly with µSL is the uncontrolled cure depth of the UV light when fabricating down-facing surfaces. To overcome this problem, light absorber is commonly used to control the cure depth. Yet the influence of light absorber on the dimension accuracy of manufactured parts is not fully understood and needs to be investigated. This work explores the effect on part accuracy of adding four different concentrations of Tinuvin®327 to PIC-100 acrylate resin without light absorber. A benchmark part has been designed to evaluate the effect of the added Tinuvin®327 on linear, position, and geometric dimensions. Results show that Tinuvin®327 has significant effects on part accuracy.